Real‐world staging computed tomography scanning technique and important reporting discrepancies in pancreatic ductal adenocarcinoma. Issue 7 (25th May 2022) - Grogan, Alexander; Loveday, Benjamin; Michael, Michael; Wong, Hui‐Li; Gibbs, Peter; Thomson, Benjamin; Lee, Belinda; Ko, Hyun Soo
Abstract: Background: Computed tomography (CT) is the first‐line staging imaging modality for pancreatic ductal adenocarcinoma (PDAC) which determines resectability and treatment pathways. Methods: Between January 2016 and December 2019, prospectively collated data from two Australian cancer centres was extracted from the PURPLE Pancreatic Cancer registry. Real‐world staging CTs and corresponding reports were blindly reviewed by a sub‐specialist radiologist and compared to initial reports. Results: Of 131 patients assessed, 117 (89.3%) presented with symptoms, 74 (56.5%) CTs included slices ≤3 mm thickness and CT pancreas protocol was applied in 69 (52.7%) patients. Initial reports lacked synoptic reporting in 131 (100%), tumour identification in 2 (1.6%) and tumour measurement in 13 (9.9%) cases. Tumour‐vascular relationship reporting was missing in 69–109 (52.7–83.2%) for regarding the key arterial and venous structures that is required to assess resectability. Initial reports had no comment on venous thrombus or venous collaterals in 80 (61.1%) and 109 (83.2%) and lacked locoregional lymphadenopathy interpretation in 13 (9.9%) cases. Complete initial staging report was present in 72 (55.0%) patients. Sub‐specialist radiological review resulted in down‐staging in 16 (22.2%) and up‐staging in 1 (1.4%) patient. Staging discrepancies were mainly regarding metastatic disease (12, 70.6%) and tumour‐vascular relationship (5, 29.4%). Conclusion: Real‐world staging imaging in PDAC patients show low proportion of dedicated CT pancreas protocol, high proportion of incomplete staging reports and no synoptic reporting. The most common discrepancy between initial and sub‐specialist reporting was regarding metastases and tumour‐vascular relationship assessment resulting in sub‐specialist down‐staging in almost every fifth case. Abstract : Centralised sub‐specialist review of real‐world CT data of 131 PDAC patients shows low proportion of adequate CT technique (56%), incomplete staging reports (45%) and no synoptic reporting (100%). Centralised sub‐specialist review identified staging discrepancies in 24%, with differences predominantly arising in reporting of metastases and tumour‐vascular relationship. Real‐world sub‐optimal CT technique, lack of synoptic and high incomplete staging reporting present barriers to accurate staging, determining resectability and optimal care in PDAC.